Comparative efficacy of five most common traditional Chinese medicine monomers for promoting recovery of motor function in rats with blunt spinal cord injury: a network meta-analysis - Xu, Luchun; Yang, Yongdong; Zhong, Wenqing; Li, Wenhao; Liu, Chen; Guo, Ziwei; Yu, Xing (Frontiers in Neurology, 2023)
Objective: This research employed a network meta-analysis (NMA) to examine the effectiveness of five traditional Chinese medicine (TCM) monomers for promoting motor function recovery in rats with blunt spinal cord injury (SCI).: Wangfang, China National Knowledge Infrastructure, Web of Science, Embase, Chinese Scientific Journal Database, PubMed, and the Chinese Biomedical Literature Databases were searched for retrieving relevant articles published from their inception to December 2022. Two reviewers performed screening of search results, data extraction, and literature quality assessment independently. Results: For this meta-analysis, 59 publications were included. Based on the recovery of motor function at weeks 1, 2, 3, and 4 in NMA, almost all TCM groups had significantly increased positive